The effects of combined training on tennis-specific performance in young tennis players - Gülşah Şahin; Osman Kurttekin (Turkish Journal of Kinesiology)
Tennis players engage in strength training to improve their tennis-specific skills and reduce the risk of injury during matches. However, this approach may not adequately develop tennis-specific skills and could potentially increase the risk of injury among young players. There is a need to examine new methods that will both support technical development and be easily tolerated by young tennis players. The aim of this study was to investigate the effects of tennis training combined with core exercises on the tennis-specific skills of young tennis players. Twenty young tennis players participated in this study. They were divided into two groups: the training group (n=10, age 14.30 years) and the control group (n=10, age 14.00 years). The training group (TRAIN) participated in a combined training program of core stability and tennis training, while control group (CONT) participated in tennis training program. Both groups trained for three sessions per week over eight weeks. Tennis performance was assessed at the baseline and after eight weeks. Forehand and backhand depth (p=0.005; ES=0.25), volley (p=0.009; ES=0.33), forehand and backhand accuracy (p=0.007; ES=1.39) and service performance (p=0.021; ES=1.78) improved significantly after training program in TRAIN group (p < 0.05). The changes in volley, forehand and backhand accuracy, service test scores were not significant after training program in CONT group (p > 0.05). The combined training program, utilizing portable and lightweight equipment near the training court, has been shown to effectively enhance tennis-specific performance. This model demonstrates significant benefits for the development of tennis-related skills.